Whitepaper on talent management and succession planning in higher learning institutions in Malaysia - Azman, Amelia Wong; Mohd Mustafah, Yasir; Musa, Muhammad Adli; Abdul Ghani, Zurina; Wan Abdullah, Wan Najihah Nurashikin; Wan Zulkifle, Wan Zahidah (IIUM Leadership Centre, 2025)
It is well-established that succession planning is a process of identifying high-potential candidates for key positions. These candidates typically undergo a series of evaluations and targeted training programs to develop the skills needed to step into the role when the time comes. Succession planning is crucial for several reasons, including ensuring leadership continuity with qualified candidates and reducing the risks associated with the sudden departures of individuals in critical positions. In fact, these two factors can be the most plausible causes of instability in a public Higher Education Provider (HEP) in Malaysia.